IMPROVING THE STORYTELLING SKILLS OF CHILDREN AGED 4–5 YEARS THROUGH THE INTERACTIVE STORYTELLING METHOD AT TK AL MAULANA - Dewi Hendrawati; Ningrum, Desy Ayu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2026)
This study aimed to improve the storytelling ability of children aged 4–5 years through the implementation of the interactive storytelling method at TK Al Maulana, Central Jakarta. Storytelling ability is an important aspect of early childhood language development, as it supports children’s confidence in speaking, vocabulary mastery, fluency, and ability to organize stories coherently. This study employed a classroom action research design conducted in two cycles involving 15 children in Class A. Data were collected through observation, documentation, and field notes, and were analyzed descriptively based on the percentage of children achieving the expected level of development. The findings showed a gradual improvement in children’s storytelling ability across the research stages. In the pre-cycle, only 33% of children achieved the expected development level. After the implementation of storytelling activities using picture storybooks in Cycle I, the percentage increased to 40%. A more significant improvement was found in Cycle II, in which the use of hand puppets increased the percentage to 86%. These findings indicate that the interactive storytelling method was effective in improving children’s storytelling ability. Therefore, this method can be considered an appropriate and engaging learning strategy to support oral language development in early childhood education.